A Comparative Analysis of Electricity Companies’ Sustainability Reporting in Australia and India - Mehadi Mamun (Journal of Accounting, Business and Management (JABM), 2023)
This study compares the sustainability reporting efforts by electricity companies in developed (Australia) and emerging (India) economies. Using the GRI G4 sector-specific guidelines for electric utilities on the 2018/2019 annual reports, stand-alone sustainability reports, corporate social responsibility (CSR) reports, and corporate websites, the study finds that the compliance rates with the categories of sustainability reporting in the Indian electricity companies are far low compare to the Australian electricity companies. Overall, the disclosure is low in both countries as the highest compliance rate in Australia is 63.7% and the lowest compliance rate is 43.6%, while in the case of India, the highest compliance rate is 45.7% and the lowest compliance rate is 28.5%. Considering that electric utilities provide essential services to society and have a significant influence on sustainable development, such a low disclosure, particularly by Indian companies, could lead the efforts to gain stakeholders’ legitimacy and sustainable development to crumble.